SEMANTIC FEATURES OF AGRICULTURAL LEXICON IN THE UZBEKISTAN EXPLANATORY DICTIONARY (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the semantic features of agricultural lexicon in explanatory dictionaries of the Uzbek language. The study studies the semantic structure of terms, their monosemantic and polysemantic properties, and their mutual relationships based on the phenomenon of synonymy. The place of agricultural terms in the lexical-semantic system, the processes of their expansion and specialization of meaning are scientifically substantiated. The national-cultural components and linguocultural characteristics of terms are also analyzed. The semantic accuracy of the terms given in explanatory dictionaries, the completeness of the explanations, and their practical application are evaluated as important criteria. The results of the study serve to systematically study agricultural lexicon, create a semantically complete description of terms, and improve lexicographic practice.